Disaster Reporting in Indonesian National Online Media: Agenda Setting and Sentiment Analysis - Rasyid, Erwin; Saharuddin, Erni; Rohmadani, Zahro Varisna (UI Scholars Hub, 2024)
In the context of disasters, the mass media is one of the main sources of information for the community. Mass media, as a communication channel, can be utilized as a disaster management system to mitigate the impact of disaster risk. However, disaster events are often treated as commodities by the mass media to attract audience attention. This study analyzes the agenda-setting and sentiment of disaster news coverage by national online media in Indonesia. It uses the Agenda-Setting Theory of McCombs and Shaw to explore how media agenda-setting relates to disaster issues. This research employs a descriptive quantitative approach using sentiment analysis. Data collection is conducted through text mining. The study results show that disaster news by online media in Indonesia is presented with various sentiments: positive, neutral, and negative. The agenda-setting of disaster news coverage across different online media portals in Indonesia is also quite diverse.